(untitled) (Journal of Universal Science Research, 2024)
This article examines the importance of vitamins for human health, their biological functions and their role in the body. The negative consequences of a deficiency of various vitamins and methods of their elimination are analyzed. Recommendations are also given on the sources of vitamins, the amount of daily needs and their correct use. The article includes measures to prevent and treat vitamin deficiency-related diseases and focuses on the role of vitamins in a healthy lifestyle.